KONSEP TRICKLING DOWN DAN POLARISASI EFFECT PADA PEMBANGUNAN DAN PARIWISATA DI KABUPATEN BADUNG, BALI - Made Ratna Witari; Agus Wiryadhi Saidi (Fakultas Sains dan Teknologi Universitas Ngurah Rai, 2023)
Economic activity that occurs in a region will affect how the development of development in the region. There are points of economic growth centers that will have an impact on the surrounding area. The influence in question can be in the form of the surrounding area also developing or even being left behind. There are various types of economic activity, one of which is economic activity in the tourism sector. This research was conducted by choosing Badung Regency in Bali Province as a case study because Badung has very rapid tourism activities compared to other districts in Bali. Tourism activities in Badung are only centered on a few points which results in inequality and uneven development in the Badung area. This study aims to determine the influence of tourism development in Badung, to find out how much influence the trickling down theory and polarization effect have in Badung, and to find out the efforts that can be taken to achieve equitable economic development in Badung. The research data was obtained by conducting a literature study and the research was carried out using a qualitative approach which would later produce descriptive data. The final results of the study show that tourism activities in Badung are a vital sector on which economic development and development in Badung depend; trickling down and polarization effects occur in Badung with different regional scales; as well as the need for the development of other tourism sectors in the suburbs of Badung Regency which is supported by government policies.